(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-185-194 The article deals with the problem of teaching appeals in the lessons of the Russian language in the interrelation of three aspects: linguistic, communicative-pragmatic and linguoculturological. a model of a multicomponent exercise is presented, which includes linguistic-semantic, communicative-pragmatic, linguistic-cultural, productive-creative and research tasks. Examples of multicomponent exercises are given. It is concluded that the linguistic and cultural analysis of appeals contributes to a deeper understanding of the text, enriching the vocabulary of schoolchildren. Key words: Russian Russian language teaching, speech etiquette, linguoculturological analysis of appeals, model of multicomponent exercise in the Russian language